FUNCTIONAL SHORT TERM RECOVERY FACTORS IN PATIENTS WITH STROKE A RETROSPECTIVE OBSERVATIONAL COHORT STUDY (International Journal of Physiotherapy, 2015)
Background: The potential for early functional recovery in stroke patients is the basis for treatment choices and drives the rehabilitation. In this study we aimed to determine the predictive factors for short-term functional recovery in stroke patients admitted in a rehabilitation clinic.Methods: We conducted an analytical, observational, retrospective cohort study on 108 stroke patients at Campolongo Hospital for Rehabilitation. The short-term functional recovery of stroke patients has been studied by the Motricity Index (MI) and the Trunk Control Test (TCT) in respect of motor recovery, and the Functional Independence Measure (FIM) scale about disability. The influence of predictors on short-term functional recovery has been studied by Chi square test.Results: All patients showed a good functional recovery at discharge. Statistically significant correlations have been found between patient’s age and the lack of trunk control at discharge (p = 0.0305), between patient’s age and the value of the Motricity Index at discharge (p = 0.0093), between the presence of aphasia and the severity of motor deficit at discharge (p = 0.0397), between the presence of neglect and the severity of motor deficit at both entry and discharge (p = 0.0051 and p = 0.0031).Conclusion: Our experience suggests that a predictive model of the short-term functional prognosis in early stroke patients allows for the optimization of the treatment and the rehabilitation taking charge. The final result will be an improvement of the patient’s satisfaction and a rationalization in the use of available resources.